New models of religious understanding - Ellis, Fiona (Oxford University Press, 2018)
What does it mean to understand the world religiously? How is such understanding to be distinguished from scientific understanding? What does it have to do with religious practice, transfiguring love, and spiritual well-being? 'New models of religious understanding' investigates these questions to set a new and exciting agenda for philosophy of religion. Featuring contributions from leading scholars in the field, the volume cuts across the supposed divide between analytic and continental approaches to the subject and engages the interest of a broad range of philosophical and theological readers